2013
DOI: 10.1016/j.ygyno.2013.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Selection and validation of endogenous controls for microRNA expression studies in endometrioid endometrial cancer tissues

Abstract: In conclusion, we suggest that average expression of those snoRNAs could be used as a reliable endogenous control in microRNA qPCR studies in endometrioid endometrial cancer. In addition to identifying suitable endogenous controls in EEC, our study presents an appropriate strategy for validation of candidate reference genes for any microRNA qPCR study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 40 publications
3
56
0
2
Order By: Relevance
“…For relative quantification of miRNA expression data were normalized using geometric mean of expression of experimentally chosen, stable endogenous controls RNU48, RNU44, U75 and U6 which were previously experimentally validated [12]. …”
Section: Methodsmentioning
confidence: 99%
“…For relative quantification of miRNA expression data were normalized using geometric mean of expression of experimentally chosen, stable endogenous controls RNU48, RNU44, U75 and U6 which were previously experimentally validated [12]. …”
Section: Methodsmentioning
confidence: 99%
“…Two small nucleolar RNAs, RNU44 (ID 001094) and RNU48 (ID 001006) showing stable expression in human endometrium [21] were used as endogenous controls. cDNA synthesis was conducted from miRNA enriched RNA fraction with TaqMan MicroRNA Reverse Transcription Kit (Applied Biosystems, California, US).…”
Section: Methodsmentioning
confidence: 99%
“…This finding indicates that some of these miRNAs could be, directly or indirectly, responsible for VEGF-A levels in endometrioid EC. A microarray study done by Torres et al [37] revealed regulation of several miRNAs in EEC tissues compared to normal endometrium. All miR-200 family members (miR-141, miR-200a, miR200b, miR-200c, and miR-429) were significantly upregulated, mostly in early stages of EEC.…”
Section: Endometrial Tumorsmentioning
confidence: 99%
“…Research into miRNAs thus carries great potential for a noninvasive diagnosis because it is, nowadays, possible to achieve miRNAs from the patients' plasma, and furthermore, aberrant expression can be also proven. For example, increased levels of miR-135b and miR-205 and decreased level of miR-30a-3p and miR-21 were identified in the plasma of EC patients, whereby after hysterectomy, levels of miR-135, miR-205, and miR-30a-3p decreased [39] respectively; signatures from EEC patients plasma-miR-9/miR-1228 and miR-9/miR92a-were also identified [37].…”
Section: Endometrial Tumorsmentioning
confidence: 99%